University Financial Management Performance Evaluation Based on Fuzzy Logic Expert System - Ying, Yue; Zhi, Hui (Informatica, 2024)
The purpose of this study is to develop a performance evaluation model of university financial management based on fuzzy logic expert system, so as to provide accurate and comprehensive evaluation results and decision support. Through a comprehensive analysis of relevant literature, this paper first introduces the importance of financial management in universities and its role in performance evaluation, and discusses the necessity, challenges and existing evaluation models of performance evaluation. Then, the theoretical basis and practical application of fuzzy logic, as well as the basic concept and application field of expert system are expounded in detail. Aiming at the present situation of financial management performance evaluation in colleges and universities, this paper summarizes the current performance evaluation methods and analyzes their advantages and disadvantages. Further, the construction process of performance evaluation model based on fuzzy logic expert system is proposed, including the principle of fuzzy logic expert system, its application in performance evaluation and the model construction of financial management in colleges and universities. To verify the validity of the model, empirical studies of simulated data were conducted, including data collection, processing and analysis, as well as presentation and analysis of empirical research results. Finally, the effectiveness of the model is evaluated quantitatively and qualitatively, the feasibility and application scenarios of the model are analyzed, and the existing problems and solutions are discussed. This study provides a new method and tool for financial management performance evaluation in colleges and universities, which has important theoretical and practical significance.